Regulation of pharmaceutical innovation : - Peltzman, Sam (American Enterprise Institute for Public Policy Research, 1974)
The production of these effects would not necessarily tell us anything about the costs and benefits of the 1962 amendments. The costs and benefits would depend on the value of the particular drugs kept off the market by the amendments and the value of the information on new drugs generated by more extensive drug testing.